Disentangling the genetic overlap between cholesterol and suicide risk. (December 2018) - Knowles, Emma; Curran, Joanne; Meikle, Peter; Huynh, Kevin; Mathias, Samuel; Göring, Harald; VandeBerg, John; Mahaney, Michael; Jalbrzikowski, Maria; Mosior, Marian; Michael, Laura; Olvera, Rene; et al.
Abstract Suicide is major public health concern; one million individuals worldwide die by suicide each year of which there are many more attempts. Thus, it is imperative that robust and reliable indicators, or biomarkers, of suicide risk be identified so that individuals at risk can be identified and provided appropriate interventions as quickly as possible. Previous work has revealed a relationship between low levels of circulating cholesterol and suicide risk, implicating cholesterol level as one such potential biomarker, but the factors underlying this relationship remain unknown. In the present study, we applied a combination of bivariate polygenic and coefficient-of-relatedness analysis, followed by mediation analysis, in a large sample of Mexican-American individuals from extended pedigrees [N = 1897; 96 pedigrees (average size = 19.17 individuals, range = 2–189) 60% female; mean age = 42.58 years, range = 18–97 years, sd = 15.75 years] with no exclusion criteria for any given psychiatric disorder. We observed that total esterified cholesterol measured at the time of psychiatric assessment shared a significant genetic overlap with risk for suicide attempt (ρ g = −0.64, p = 1.24 × 10−04 ). We also found that total unesterified cholesterol measured around 20 years prior to assessment varied as a function of genetic proximity to an affected individual (h 2 = 0.21, se = 0.10, p = 8.73 × 10−04 ;β suicide = −0.70, se = 0.25, p = 8.90 × 10−03 ). Finally, we found that the relationship between total unesterified cholesterol and suicide risk was significantly mediated by ABCA-1-specific cholesterol efflux capacity (β suicide-efflux = −0.45, p = 0.039;β efflux-cholexterol = −0.34, p < 0.0001;β indirect = −0.15, p = 0.044). These findings suggest that the relatively well-delineated process of cholesterol metabolism and associated molecular pathways will be informative for understanding the neurobiological underpinnings of risk for suicide attempt.